Efektivitas Latihan Core Stability Terhadap Kemampuan Shooting Dalam Permainan Petanque - Isyani Isyani; Intan Primayanti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Ability to shoot of extracurricular petanque students at MA Yahdinu Masbagik East Lombok is so weak, there is a impact of arm muscle strength and body balance by players. In carrying out the shooting, the related components that affect the shooting are, the ball grip, the position of the body leading to the target, the statistical balance of the limbs, the low body position and leaning forward, the ball relay, continue. The balance when throwing strongly influences an petanque atlet. Another thing that concerns us is training the core muscles because the center of balance of the human body  or the center of gravity of the human body is on which parts are attached to these muscles. The research design used in this study was a pretest posttest group design with sampling technique Purposive samples obtained as many as 20 samples. The method of collecting data uses a firing test based on the standard FIPJP. Data analysis techniques using the T-test Paired test with SPSS 17. The results of the data analysis showed a significant effect on Core Stability training on improving shooting ability in petanque sports, this is evidenced from the t-test results of 9,815 with a significance of 0.00 < α 0.05.